AFLP analysis of genetic diversity in determinate and indeterminate snap bean accessions - Andrade, Felipe Aranha de; Gonçalves, Leandro Simões Azeredo; Miglioranza, Édison; Ruas, Claudete de Fátima; Ruas, Paulo Mauricio; Takahashi, Lúcia Sadayo Assari (Acta Scientiarum. Agronomy, 2016)
The present study aimed to estimate and characterize the genetic divergence between determinate and indeterminate snap bean accessions from the Universidade Estadual de Londrina (UEL) germplasm bank based on amplified fragment length polymorphism (AFLP) markers. A total of 40 and 32 accessions with determinate and indeterminate growth habits, respectively, were characterized for this purpose. Seven combinations of primers corresponding to EcoR1 and Mse1 were tested for the AFLP analysis, and the combinations E-AAG/M-CTC, E-ACT/M-CTT and E-ACC/M-CTT were selected. These selective AFLP combinations revealed 485 informative loci in total, and the combination E-ACC/M-CTT detected the greatest number of informative loci (49%). The analysis of dissimilarity frequency distribution showed that the distribution was uniform, ranging from 0.1285 to 0.7310 with a mean of 0.4801, and the accessions with indeterminate growth habits exhibited greater variability than the accessions with determinate growth habits. The clustering UPGMA, PCoA and Bayesian analyses showed the formation of two large clusters, wherein there is a possible association between snap bean growth habit and gene pool. The determinate accessions may be more closely associated with the Andean gene pool, while the indeterminate ones may be associated with the Mesoamerican gene pool. The Bayesian analysis showed accessions intermediate to both groups, suggesting introgression between the Andean and Mesoamerican gene pools.